A high gas transfer efficiency microfluidic oxygenator for extracorporeal respiratory assist applications in critical care medicine. Issue 8 (4th April 2021) - Gimbel, Alla A.; Hsiao, James C.; Kim, Ernest S.; Lewis, Diana J.; Risoleo, Thomas F.; Urban, Joseph N.; Borenstein, Jeffrey T.
Abstract: Advances in microfluidics technologies have spurred the development of a new generation of microfluidic respiratory assist devices, constructed using microfabrication techniques capable of producing microchannel dimensions similar to those found in human capillaries and gas transfer films in the same thickness range as the alveolar membrane. These devices have been tested in laboratory settings and in some cases in extracorporeal animal experiments, yet none have been advanced to human clinical studies. A major challenge in the development of microfluidic oxygenators is the difficulty in scaling the technology toward high blood flows necessary to support adult humans; such scaling efforts are often limited by the complexity of the fabrication process and the manner in which blood is distributed in a three‐dimensional network of microchannels. Conceptually, a central advantage of microfluidic oxygenators over existing hollow‐fiber membrane‐based configurations is the potential for shallower channels and thinner gas transfer membranes, features that reduce oxygen diffusion distances, to result in a higher gas transfer efficiency defined as the ratio of the volume of oxygen transferred to the blood per unit time to the active surface area of the gas transfer membrane. If this ratio is not significantly higher than values reported for hollow fiber membrane oxygenators (HFMO), then the expected advantage of the microfluidic approach would not be realized in practice, potentially due to challenges encountered in blood distribution strategies when scaling microfluidic designs to higher flow rates. Here, we report on scaling of a microfluidic oxygenator design from 4 to 92 mL/min blood flow, within an order of magnitude of the flow rate required for neonatal applications. This scaled device is shown to have a gas transfer efficiency higher than any other reported system in the literature, including other microfluidic prototypes and commercial HFMO cartridges. While the high oxygen transfer efficiency is a promising advance toward clinical scaling of a microfluidic architecture, it is accompanied by an excessive blood pressure drop in the circuit, arising from a combination of shallow gas transfer channels and equally shallow distribution manifolds. Therefore, next‐generation microfluidic oxygenators will require novel design and fabrication strategies to minimize pressure drops while maintaining very high oxygen transfer efficiencies. Abstract : Photograph of a 14‐layer microfluidic oxygenator constructed by replica molding of PDMS (Poly(DiMethylSiloxane)) films from a photolithographically defined microfabricated master mold, during gas transfer testing with whole bovine blood. The blood channel network for this device represents a branching architecture designed to mimic the smooth flow patterns seen in physiological vasculature. Oxygen transfer testing of these devices demonstrates oxygen transfer efficiencies in excess of 300 mL/min/cm 2, higher than any values reported in the literature.